Spatial dynamics of three estuarine predatory fishes in a subtropical estuary - Paco Fontaine; Christine C. Jensen; Philip Matich; Jay R. Rooker; R. J. David Wells (Marine Biology, 2026)
Understanding movement and habitat use patterns of co-occurring predatory fishes is crucial for effective conservation and management of estuarine ecosystems, where dynamic seasonal shifts and species interactions play crucial roles in shaping community structure. Using acoustic telemetry and network analysis, we compared the movements of alligator gar ( Atractosteus spatula , n = 13), bull sharks ( Carcharhinus leucas , n = 12), and Atlantic stingrays ( Hypanus sabinus , n = 11) within and outside the boundaries of a large estuary (Galveston Bay Complex, GBC) in the northwestern Gulf of Mexico. Habitat use varied seasonally for all species, though these patterns have been affected by tagging locations and receiver deployment. Alligator gar were detected year-round in the GBC, with seasonal variation likely driven by environmental conditions and prey availability. Bull sharks displayed seasonal migrations, with increased estuarine use during warmer months and a notable shift out of the GBC to southern bays in the winter. Atlantic stingrays exhibited restricted movement within the GBC during the summer, with few detections in other seasons potentially attributable to receiver coverage, tag retention and predation. Interspecific overlap in habitat use was highest between alligator gar and bull sharks, and lower with Atlantic stingrays. Intraspecific overlap was observed across all three species but was most extensive for bull sharks, suggesting that increased overlap may intensify competition, possibly driving size-based habitat partitioning. Our findings highlight the importance of habitat connectivity and seasonal dynamics for co-occurring predatory fishes within an estuary.